Fair Settlement as Basis for Ethical Integrity of Mediation - Natia Chitashvili (Alternative Dispute Resolution Yearbook, 2016)
The article offers study of fair mediation settlement, as an ethical and normative category, as one of the fundamental principles of mediation, on the basis of review of mediation acts and Codes of Ethics of EU countries and USA. At the stage of improving mediation legal framework and formation of ethical regulations in Georgia, it is essential to develop research-based recommendations for the purpose of approximation of domestic legal framework with EU legislation. Public interest for protecting trust of society towards mediation stipulates assigning to a mediator the function of a guarantor of fair settlement.